Strategi Fasilitator dalam Program Perlindungan Anak Terpadu Berbasis Masyarakat di Kota Palu, Indonesia - Meisya Amir; Nurasia Munir; Ardillah Abu; Suharto Suharto (Jurusan Pengembangan Masyarakat Islam Fakultas Dakwah dan Komunikasi Islam, UIN Datokarama Palu., 2025)
This study examines the Facilitator Strategies in the Integrated Community-Based Child Protection Program (PATBM) Against Child Abuse in Duyu Subdistrict, Tatanga District. The background of the study stems from cases of child abuse that require the active role of facilitators in prevention, handling, and recovery of victims. This research focuses on facilitator strategies for children who experience violence through the PATBM Program and identifies the programs implemented in Duyu Subdistrict. The study uses a qualitative descriptive approach, with data collected through observation, in-depth interviews with the PATBM chairperson and facilitators, and documentation. Data analysis was carried out interactively through data reduction, presentation, and conclusion drawing, accompanied by validity checks using triangulation of sources, methods, researchers, and theories. The findings show that facilitator strategies include emotional and psychological approaches, case reporting and facilitation, coordination with traditional institutions and local government, and monitoring of areas prone to child abuse. The activities implemented include socialization, case assistance, capacity building for facilitators and PATBM members, as well as voluntary and non-formal activities. The study implies that the local government should recruit more members so that the reporting and follow-up mechanisms can function optimally.